2012
DOI: 10.5194/os-8-657-2012
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional modelling of wave-induced current from the surf zone to the inner shelf

Abstract: Abstract. We develop and implement a new method to take into account the impact of waves into the 3-D circulation model SYMPHONIE (Marsaleix et al., 2008(Marsaleix et al., , 2009a following the simplified equations of , which use glm2z-RANS theory (Ardhuin et al., 2008c). These adiabatic equations are completed by additional parameterizations of wave breaking, bottom friction and wave-enhanced vertical mixing, making the forcing valid from the surf zone through to the open ocean. The wave forcing is performed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 79 publications
1
29
0
2
Order By: Relevance
“…Bennis et al [2011] confirmed the ability of A08 formulation to provide the vertical structure of the flow by numerical modeling of an adiabatic configuration. Michaud et al [2012] further showed the consistency of the solution obtained from A08 formulation with results from Haas and Warner [2009] and Uchiyama et al [2010] in the case of obliquely incident waves breaking on a plane beach. Model results were further applied to a realistic configuration on the French Mediterranean coast.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bennis et al [2011] confirmed the ability of A08 formulation to provide the vertical structure of the flow by numerical modeling of an adiabatic configuration. Michaud et al [2012] further showed the consistency of the solution obtained from A08 formulation with results from Haas and Warner [2009] and Uchiyama et al [2010] in the case of obliquely incident waves breaking on a plane beach. Model results were further applied to a realistic configuration on the French Mediterranean coast.…”
Section: Introductionmentioning
confidence: 99%
“…WWIII has been widely validated at global and regional scales [e.g., Tolman, 2002;Ardhuin et al, 2008aArdhuin et al, , 2010, and more recently in nearshore areas [e.g., Filipot and Michaud et al, 2012;Ardhuin et al, 2012]. The model solves the spectral balance equation for the wave action density N, with source terms S in , S nl , S oc , and S bot for wind input, nonlinear four-waves interactions, wave breaking dissipation and bottom friction dissipation, respectively.…”
Section: Wave Model Implementationmentioning
confidence: 99%
“…Wave-current interaction has been a topic of many studies recently (Ardhuin et al, 2008;Mellor, 2003Mellor, , 2008Mellor, , 2011Kumar et al, 2012;Michaud et al, 2012;Zodiatis et al, 2015). Mellor (2003Mellor ( , 2005Mellor ( , 2008 extended the radiation stress formulation based on the linear wave theory of Longuet-Higgins and Stewart (1964).…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of both methods by Moghimi et al (2013) showed that the results are similar for longshore circulations, but radiation stress enhanced offshore-directed transport in wave shoaling regions. Many other studies addressed the role of the interaction between wind waves and circulation in the model simulations (Michaud et al, 2012;Barbariol et al 2013;Brown et al, 2011;Katsafados et al, 2016;Bolaños et al, 2011Bolaños et al, , 2014Röhrs et al, 2012).…”
Section: Introductionmentioning
confidence: 99%